Mekanisme Survival Petani “Gurem” pada Masa Pandemi COVID-19 - Ambayu Sofya Yuana; Siti Kholifah; Mohamad Anas (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2020)
Small-scale farmers in Tlogosari, Pagak, Malang have many limitations, especially economically. Instead of wanting to improve economic prosperity, small-scale farmer makes changes to the commodities they grow from sugar cane to sengon (Paraserianthes falcataria (L) or albizia). But the change in this commodity has an impact on changing the pattern of short to long harvests. This condition has increasingly resulted in the economic downturn of the farming family, coupled with the existence of the COVID-19 pandemic, making farmers increasingly powerless. This research focuses on the survival mechanism of small-scale farmers who switch commodities from sugar cane to sengon during the COVID-19 pandemic. This study uses James Scott's theory of the ethics of subsistence as a knife of analysis and uses a qualitative approach with a case study method. The research informants were determined by purposive sampling with the criteria of small-scale farmer informants who were affected by the COVID-19 pandemic due to the change of sugarcane commodity to sengon. The price of sengon during the COVID-19 pandemic dropped dramatically due to many factories closed, so farmers are also confused looking for sengon buyers. This condition makes small-scale farmers feel like poor famine. Faced with such conditions, smallholders do survival by other work, namely making gatot, tiwul, and corn grits (ampok) as a profitable employment opportunity in the future of COVID-19